2015
DOI: 10.1039/c5ay00012b
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical analyzer for in situ flow determination of Pb(ii) and Cd(ii) in lake water with on-line data transmission and a global positioning system

Abstract: A potentiostat/galvanostat with wireless data transmission and a GPS receiver was applied to in situ flow analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…On the other hand, the MCFA-MPA system presented an analytical frequency six times higher than the FBA-DPASV. Shortly after, the same research group presented a study for in situ simultaneous determination of Cd 2+ and Pb 2+ in natural waters, employing a flow-batch analysis with square-wave anodic stripping voltammetric detection (FBA-SWASV) (Bezerra dos Santos et al, 2015). The developed electrochemical analyzer was capable of on-line data transmission and used a solar board as renewable energy source.…”
Section: Bdd Electrode Coupled To Fia Systemsmentioning
confidence: 99%
“…On the other hand, the MCFA-MPA system presented an analytical frequency six times higher than the FBA-DPASV. Shortly after, the same research group presented a study for in situ simultaneous determination of Cd 2+ and Pb 2+ in natural waters, employing a flow-batch analysis with square-wave anodic stripping voltammetric detection (FBA-SWASV) (Bezerra dos Santos et al, 2015). The developed electrochemical analyzer was capable of on-line data transmission and used a solar board as renewable energy source.…”
Section: Bdd Electrode Coupled To Fia Systemsmentioning
confidence: 99%
“…This procedure performs an electrochemical cleaning of the electrode surface. 16–21 After the treatment, cyclic voltammetry using 0.1 mmol L −1 K 3 [Fe(CN) 6 ] in 0.1 mol L −1 KCl was carried out in order to verify the electrochemical behavior of the pretreated BDDE, by checking the electrochemical reversibility of the Fe 2+ /Fe 3+ redox pair. In sequence, before using the pulse voltammetric method for 2,4-D detection, 20 to 25 cyclic voltammograms were performed at 50 mV s −1 in a potential range from 0 to 1.8 V vs. Ag/AgCl (3.0 mol L −1 KCl) to stabilize the BDDE surface.…”
Section: Methodsmentioning
confidence: 99%
“…The BDDE has a low capacitive current, wide work potential range, low adsorption, good thermal stability, good electrical conductivity and possibility of chemical modification on its surface which allows it to detect compounds at very low detection limits. 15–21 The BDDE has been applied for the determination of electroactive organic and inorganic species in environmental samples. 16–21 Silva et al 21 has reported on a voltammetric method using BDDE to detect Picloram herbicide in environmental waters in the Brazilian Amazon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small dosage area enables very low sample consumption, in some cases sample volumes can be smaller than 10 μL. The compact size and excellent selectivity and sensitivity enable incorporation of SPE into the flow automatically [ 28 ] or robotic systems [ 29 ] for on-site analysis. Furthermore, these electrodes are suitable for environmental monitoring of metal ions [ 30 ] and multiplexing (sensor array) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%